2011
DOI: 10.1039/c1sm05210a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of anodic electrodeposition of calcium alginate

Abstract: Stimuli-responsive polysaccharides that can undergo a sol-gel transition in response to localized electrical signals provide a unique opportunity to electroaddress biological components at device interfaces. Most polysaccharide electroaddressing mechanisms use electrochemical reactions to generate pH gradients that can locally neutralize the polysaccharide and induce its reversible sol-gel transition to form a hydrogel film adjacent to the electrode surface. The calcium-responsive polysaccharide alginate is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
88
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 40 publications
1
88
0
Order By: Relevance
“…The strength of the gel depends on the alginate composition and the cross-linker ions, which is added during the polymerization process. 16 However, since the electrochemical technique was affected by material diffusion to the electrode surface, the thickness of the film becomes an important factor. The influence of the film thickness was investigated using a total number of 2.56 × 10 8 R. mucilaginosa cells, which are immobilized in various film thicknesses.…”
Section: Examination Of Oxygen Sensors and Immobilization Of R Mucilmentioning
confidence: 99%
See 3 more Smart Citations
“…The strength of the gel depends on the alginate composition and the cross-linker ions, which is added during the polymerization process. 16 However, since the electrochemical technique was affected by material diffusion to the electrode surface, the thickness of the film becomes an important factor. The influence of the film thickness was investigated using a total number of 2.56 × 10 8 R. mucilaginosa cells, which are immobilized in various film thicknesses.…”
Section: Examination Of Oxygen Sensors and Immobilization Of R Mucilmentioning
confidence: 99%
“…Ca 2+ ), alginate turns to gel formation through the crosslink carboxylate groups in the G-block of alginate, which leads to the formation of alginate macromolecular chain crosslinking. [16][17][18] In addition to this unique gel formation, the flexible structure and highly adsorbent of the gel establishes it as a suitable matrix to immobilize yeast, enzyme, and living cells. 16 Therefore, it was expected that no extreme change occurrs on R. mucilaginosa Y-181 when it is being immobilized as well as during storage after immobilization.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a biocompatible polysaccharide of sodium alginate, which can form a calcium alginate gel in the presence of calcium ions (Ca 2+ ), is widely used to entrap and immobilize prokaryotes and eukaryotic cells in 3D hydrogel structures [3][4][5]. Among these fabrication methods to form alginate hydrogels, electroaddressing is an attractive technique due to its ability to deposit alginate hydrogels [6][7][8][9][10][11][12][13] at specific addresses and in specific shapes with a controllable pattern on the preformed metal thin-film electrode surfaces. Payne et al [8,11] reported the electroaddressing of calcium alginate hydrogels, with the ability to entrap viable cell populations within the electrodeposited films.…”
Section: Introductionmentioning
confidence: 99%